Pengaruh Customer Relationship Management terhadap Loyalitas Ibu Hamil pada Pelayanan Persalinan (Studi di RS Hermina Tangkubanprahu Malang) - Estiningsih, Agnes Widayu; Hariyanti, Tita (Universitas Brawijaya, Indonesia, 2013)
The reseach goals are to test whether there is influence of Customer Relationship Management (CRM) to customer loyality. The research method was observasional analitic research with cross sectional study. The respondents 42 pregnant mother in the CRM program. CRM variables consist of people, process and technology was colect with self administered quesionare . Data was analyzed with the multiple linierregression and processing of data using SPSS 18 software. The result showed that CRM affects pregnant mother loyality of labor service.